2015
DOI: 10.1158/1055-9965.epi-14-0895
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Is Effective for the Detection of EGFR Mutation in Non–Small Cell Lung Cancer: A Meta-analysis

Abstract: Background: Circulating tumor DNA (ctDNA) has offered a minimally invasive and feasible approach for detection of EGFR mutation for non-small cell lung cancer (NSCLC). This meta-analysis was designed to investigate the diagnostic value of ctDNA, compared with current "gold standard," tumor tissues.Methods: We searched PubMed, EMBASE, Cochrane Library, and Web of Science to identify eligible studies that reported the sensitivity and specificity of ctDNA for detection of EGFR mutation status in NSCLC. Eligible s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(127 citation statements)
references
References 56 publications
7
116
4
Order By: Relevance
“…IC: 0.51-0.72) and specificity of 0.96 (95% IC: 0.93-0.98) are consistent with our results. 19 In contrast, Dawson et al reported mutation detection in 18 of the 19 women and in 80 of the 97 plasma samples (82%) analyzed; however, these researchers used larger blood samples (30 ml each vs. 0.4-2 ml in our study). 17 The use of dPCR for ctDNA analysis has been reported previously for MBC, but only after deep sequencing of the primary tumor to define the non-recurrent driver mutations of TP53, PI3KCA or PTEN.…”
Section: Short Reportcontrasting
confidence: 62%
“…IC: 0.51-0.72) and specificity of 0.96 (95% IC: 0.93-0.98) are consistent with our results. 19 In contrast, Dawson et al reported mutation detection in 18 of the 19 women and in 80 of the 97 plasma samples (82%) analyzed; however, these researchers used larger blood samples (30 ml each vs. 0.4-2 ml in our study). 17 The use of dPCR for ctDNA analysis has been reported previously for MBC, but only after deep sequencing of the primary tumor to define the non-recurrent driver mutations of TP53, PI3KCA or PTEN.…”
Section: Short Reportcontrasting
confidence: 62%
“…Another meta-analysis of 25 studies demonstrated the pooled overall sensitivity, specificity, and concordance rate of ctDNA compared to tissue as 61%, 90% and 79%, respectively (30). Qiu et al showed a pooled sensitivity and specificity of 62% and 95.9% for ctDNA to detect EGFR mutations in their meta-analysis of 27 studies involving 3,110 participants (31). The large multicenter non-interventional ASSESS study investigated the utility of ctDNA EGFR testing in the real world setting in patients with metastatic NSCLC in Europe and Japan.…”
Section: Utilizing Ctdna In Initial Diagnosismentioning
confidence: 99%
“…With regard to specific genetic alterations, one clear example is the clinical utility of the detection of EGFR mutations in the cfDNA of NSCLC patients treated with gefitinib (25) or erlotinib (26). EGFR mutations have also been shown to be of prognostic and predictive value, and patients with an activating mutation in EGFR in cfDNA have been reported to respond significantly better to TKIs (27). KRAS gene alterations detected in cfDNA have also been used as prognostic biomarkers, mainly in colorectal and pancreatic cancer (28,29).…”
Section: Circulating Free Dna (Cfdna) As Prognostic and Monitoring Tementioning
confidence: 99%